MyBotS Prototype on Social Media Discord with NLP (Baghdad Science Journal, 2021)
The continuous growth in technology and technological devices has led to the development of machines to help ease various human-related activities. For instance, irrespective of the importance of information on the Steam platform, buyers or players still get little information related to the application. This is not encouraging despite the importance of information in this current globalization era. Therefore, it is necessary to develop an attractive and interactive application that allows users to ask questions and get answers, such as a chatbot, which can be implemented on Discord social media. Artificial Intelligence is a technique that allows machines to think and be able to make their own decisions. This research showed that the discord chatbot prototype provides various services based on the results of classification testing using the SVM method with three kernels, namely Linear, Polynomial, and RBF. The test data and accuracy values prediction are the largest Liniear Kernel SVM with accuracy and error prediction values of 94% and 6%.